Penyuluhan Hukum Tentang Politik Uang Bagi Siswa Sekolah Menengah Atas Sebagai Upaya Mewujudkan Pemilih Cerdas - Sulihin, La Ode Muhamad; Abdullah, Sitti Aisah; Sirjon, Lade; Sanib, Safril Sofwan; Arfa, Arfa (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to increase legal knowledge about money politics for high school students as an effort to create intelligent voters. This activity was carried out at SMA Negeri 2 South Konawe and Madrasah Aliyah DDI Nurul Qalbi Ranomeeto. The method of implementing this community service used interactive counseling with evaluation instruments, namely pre-test and post-test. Furthermore, the data analysis technique for this community service was analyzed descriptively. The results of this community service showed that there was an increase in students' understanding of the criminal law aspect of money politics practices. Through insight into criminal regulations on money politics practices, it could guide students in acting in society in accordance with legal provisions so that it has implications for the realization of smart voters.